2021
DOI: 10.1177/02841851211011563
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of ultrashort echo time (UTE) T2* cartilage mapping in the hip: a pilot study

Abstract: Background Ultrashort echo time (UTE) T2* is sensitive to molecular changes within the deep calcified layer of cartilage. Feasibility of its use in the hip needs to be established to determine suitability for clinical use. Purpose To establish feasibility of UTE T2* cartilage mapping in the hip and determine if differences in regional values exist. Material and Methods MRI scans with UTE T2* cartilage maps were prospectively acquired on eight hips. Hip cartilage was segmented into whole and deep layers in ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
(41 reference statements)
2
5
0
Order By: Relevance
“…The mean UTE T2* values in the hip cartilage of our asymptomatic patients were similar to those seen in asymptomatic knees by Titchenal et al (16). They were, however, lower than what was found in the hips of their asymptomatic volunteers (12). These differences may be related to technical factors, including the specific scanner used and variation in the parameters of the UTE T2* mapping technique.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The mean UTE T2* values in the hip cartilage of our asymptomatic patients were similar to those seen in asymptomatic knees by Titchenal et al (16). They were, however, lower than what was found in the hips of their asymptomatic volunteers (12). These differences may be related to technical factors, including the specific scanner used and variation in the parameters of the UTE T2* mapping technique.…”
Section: Discussionsupporting
confidence: 77%
“…UTE T2* mapping is a technique that can potentially be used to assess hip cartilage in patients with FAI. The prior establishment of high inter- and intra-observer variability is helpful for consideration of adaptation of the technique and the reproducibility shown in this study further supports that as a possibility (12). Agergaard et al recently performed a study that also demonstrated high reproducibility of their UTE T2* technique (13).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Previous in vitro studies have confirmed that UTE-T2* mapping is a potential method for evaluating the quality of cartilage, as it is sensitive to the destruction of deep cartilage (12,38,39). Williams et al (22) claimed that UTE-T2* mapping has lower values in severely degraded cartilage compared to healthy cartilage.…”
Section: Discussionmentioning
confidence: 98%